INTERGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH Se-KABUPATEN BANTUL YOGYAKARTA - Laelatul Badriah; Sukati Sukati (PD PGMI se Indonesia, 2021)
Bantul Regency is one of the areas in the Yogyakarta region that has various local wisdoms to be integrated into learning at Madrasah Ibtidaiyah. There are six classifications of local wisdom in Bantul Regency which can be integrated in learning, namely 1) Local wisdom which is related to the type of food. 2) Local wisdom related to the way of the production system. 3) Local wisdom related to medicine. 4) Local wisdom related to the type of housing. 5) Local wisdom related to the type of clothing. 6) Local wisdom related to humans. This research is a field research with MI research subjects in Bantul district, amounting to 31 MI. Then MI of Bantul district is classified based on the institution that oversees it, consisting of MI under the Maarif Education Institute, MI under the Muhammadiyah Education Institute, MI under Pondok pesantren and MI under the government. Research subjects in this study were students and teachers of upper and lower classes. The process of integrating local wisdom into this learning process is the compatibility of themes and the wealth of wisdom that Bantul district has. Similarities in learning themes from the perspective of agricultural products, culture, geographic location, and community participation in realizing meaningful learning. The results of this integration are expected to form the character of students who are earlier and better. The characters that emerge from the integration of local wisdom in the learning process include honesty, responsibility, discipline, love for the country, cooperation, tolerance, and care. As for the factors that support and inhibit factors. Among the supporting factors are government regulations, both the provincial government of the Special Region of Yogyakarta and local governments, the environment and school culture, and the inhibiting factors are the achievement of the Madrasah Vision and Mission, the adequacy of Human Resources (HR), the fulfillment of facilities and infrastructure, fund management, madrasah management, and limited time.